Physician density in a two-tiered health care system - Martin Gächter; Peter Schwazer; Engelbert Theurl; Hannes Winner (University of Salzburg, Department of Social Sciences and Economics, 2011)
We investigate the density of private physicians in a two-tiered health care system, i.e., one with co-existing public and private health care providers. In particular, we analyze how the densities of private and public suppliers of outpatient health care (general practitioners and specialists) are related to each other. Using a panel of 121 Austrian districts between 2002 and 2008, we find that the density of private specialists is positively associated with the density of private general practitioners, but negatively related to the density of public general practitioners. We also observe a negative relationship between the densities of private and public general practitioners and the ones of private and public specialists, indicating competitive forces between the private and the public sector of the outpatient health care provision in Austria.
Keywords: I11; I18; L23; C23; 330; Competition in health care markets; physician location; panel econometrics